PEMANFAATAN Trichoderma sp UNTUK PENGENDALIAN PENYAKIT DAN PENINGKATAN HASIL PRODUKSI TANAMAN PADI DI NAGARI SIMABUR KECAMATAN PARIANGAN KABUPATEN TANAH DATAR - Yulmira Yanti (Jurnal Hilirisasi IPTEKS, 2021)
The Simabur Sukses Makmur farmer group is one of the active farmer groups in the Simabur village which is included in the Pariangan District, Tanah Datar Regency with the main sector only in the agricultural sector with the main crop being lowland rice. The problem that is often faced by Simabur farmers is the problem of pests and diseases which are the cause of the low growth and yield of the lowland rice plant. One of the main components of the IPM program that can be used as a biological control agent is the use of Trichoderma sp indigenous. In addition to the use of biological agents, the system or method of planting also affects the production results of the cultivated plants. The purpose of this community service is to increase public knowledge about the use of Trichoderma sp which can increase the growth and production of rice plants with the jajar legowo system. The method used in this activity is structured training and direct demonstration in the field, which will take place from June to October 2021. The results obtained from this activity are the production of grain weight/plant clump treated with Trichoderma sp is higher than the control with a difference of 42 ,45 grams. The conclusion of this activity is that the growth and yield of plants that were applied with Trichoderma were higher than those that were not treated with Trichoderma (control). The use of Trichoderma is highly recommended because in addition to being easy to obtain, it also provides a positive value for plant growth and is good for environmental technology around cultivated plants.